2018
DOI: 10.1111/dme.13769
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in the clinical effectiveness of liraglutide in Type 2 diabetes: a real‐world retrospective study conducted in Spain

Abstract: In this real-world study, we showed the effectiveness of liraglutide in improving body weight, HbA , mean systolic and diastolic blood pressure, and lipid levels. GAMMs indicated that baseline HbA and weight, time of treatment with liraglutide, diabetes duration and the use of metformin or insulin are predictors of clinical response to liraglutide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…Gomez-Peralta et al found a positive correlation between weight reduction and a higher baseline weight, longer duration of treatment with liraglutide, and the interaction between time and concomitant metformin [25]. Another real-world study found lower HbA1c reductions in patients who initiated insulin either before or around the same time as starting a GLP-1RA [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gomez-Peralta et al found a positive correlation between weight reduction and a higher baseline weight, longer duration of treatment with liraglutide, and the interaction between time and concomitant metformin [25]. Another real-world study found lower HbA1c reductions in patients who initiated insulin either before or around the same time as starting a GLP-1RA [30].…”
Section: Discussionmentioning
confidence: 98%
“…Different patterns of response have been attributed to factors such as age, liraglutide dose, baseline HbA1c, duration of T2DM, and concomitant treatments. A higher baseline HbA1c, longer duration of T2DM, and longer duration of insulin treatment have been shown to counter the effects of liraglutide [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies have examined characteristics associated with weight loss response to obesity pharmacotherapies (Table 3). A majority of these investigations involve orlistat [71][72][73][74][75][76] and GLP-1 receptor agonists (GLP1-RAs) [77][78][79][80][81][82][83][84][85] in individuals with overweight/obesity, or topiramate in individuals with seizure disorders with or without obesity. [86][87][88][89] Studies evaluating hormonal, genotypic, and neuronal predictors of weight loss response are rare.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…91 Specifically, in adults with type 2 diabetes mellitus (T2DM) prescribed GLP1-RAs, a lower hemoglobin A1c level seems to predict an improved weight loss response. 78,83 Further, a higher baseline weight status, 80,84 longer duration of treatment, 80 and previous use of dipeptidyl peptidase journals.sagepub.com/home/tae 13 4 inhibitors 84 have also been associated with better weight loss outcomes. Overall, while some predictors of weight loss response to obesity pharmacotherapy have been uncovered, there is a myriad of others yet to be elucidated.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Thus, it is likely that sequential initiation would be the more commonly adopted approach, including Patient #1 in whom liraglutide was started followed by SGLT2 inhibitor, and Patient #2 in whom liraglutide was added to existing SGLT2 inhibitor therapy. Gomez et al [15] found that a greater reduction in HbA1c and weight was observed when GLP-1 agonist was added to existing treatment with an SGLT2 inhibitor, rather than vice versa [13]-which was the approach in Patient #2.…”
Section: Discussionmentioning
confidence: 99%